Prices : Issues in Theory, Practice, and Public Policy - Phillips, Almarin; Williamson, Oliver E. (University of Pennsylvania Press, 2016)
These sixteen essays are organized around five themes: pricing implications of developments in the theory of the firm; wage-price guidelines; pricing in regulated industries; marketing models and empirical studies of pricing behavior; rationality of business pricing decisions; and implications of pricing practices for antitrust enforcement.